The Characteristics of Chitosan Derived from Lobster Shells and its Effect on Fungi Activity and Water Stability of Lobster Pellets - Ihsan, Muhsinul; Harris, Ali; Mukminah; Megawati; Purwati, Nining; Muliasari, Handa; Priyambodo, Bayu; Jones, Clive; Nankervis, Leo (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlights of Research The chitosan was successfully produced from lobster shells Panulirus homarus. The characteristics and quality of chitosan from lobster shells Panulirus homarus were observed. The anti-fungal activity of chitosan was assessed. Chitosan enhances the water stability of lobster pellets. Abstract Tropical rock lobster aquaculture is a lucrative industry that is currently limited by the lack of appropriate formulated feed. Its nocturnal, benthic feeding behavior necessitates a water-stable feed that maintains integrity under tropical marine conditions without degrading. Chitosan, a biopolymer derived from lobster (Panulirus homarus) shells, has potential applications in aquaculture as an antifungal agent and feed binder. We report on the characteristics of chitosan extracted from the exoskeleton of spiny lobsters (Panulirus homarus), including its effect on fungal activity and water stability of pellets. Chitosan was produced through three main steps: deproteination, demineralization, and deacetylation. The resulting chitosan was characterized through crude composition (AOAC methods), FTIR spectra, and scanning electron microscope (SEM), while antifungal activity was assessed through in vitro assays. Chitosan was used to coat lobster feed pellets by immersion method at different concentrations (0%, 0,5%, 1%, 1,5%, and 2%), and its impact on pellet water stability was assessed. There were three replications in fungal activity and water stability test. The yield of chitosan was 5.9 ± 0.01% of the total shell mass, with 96.99% ± 0.01 degree of deacetylation (DD). The resulting product contained 5.94 ± 0.07% moisture, 36.72 ± 0.05% ash and 2.73 ± 0.08% nitrogen. Chitosan morphology was characterized as an irregular shape with dimensions ranging from 157 to 391 µm, with a combination of striated surface textures. Increasing concentration of chitosan increased water stability of pellets up to 1.5% inclusion, while 0.5% optimized Fusarium sp. inhibition. These findings suggest that chitosan from lobster shells can be sustainably utilized to enhance feed quality, reducing fungal contamination and nutrient leaching in aquaculture systems.